2022
DOI: 10.3390/jcm11030622
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Inflammation, and Mortality in COVID-19: An Observational Study from the Public Health Care System of New York City

Abstract: Severe obesity increases the risk for negative outcomes in patients with coronavirus disease 2019 (COVID-19). Our objectives were to investigate the effect of BMI on in-hospital outcomes in our New York City Health and Hospitals’ ethnically diverse population, further explore this effect by age, sex, race/ethnicity, and timing of admission, and, given the relationship between COVID-19 and hyperinflammation, assess the concentrations of markers of systemic inflammation in different BMI groups. A retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
10
1
1
Order By: Relevance
“…Risk factors such as hypertension, diabetes, older age and obesity have been associated with worse prognosis in patients with coronavirus disease 2019 (COVID-19). Among these, hypertension is particularly important due to its high prevalence and global burden, however, the mechanisms of this association have not been fully clarified [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors such as hypertension, diabetes, older age and obesity have been associated with worse prognosis in patients with coronavirus disease 2019 (COVID-19). Among these, hypertension is particularly important due to its high prevalence and global burden, however, the mechanisms of this association have not been fully clarified [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is associated with significant lung and cardiac dysfunction, and magnesium is required for proper lung and heart function. Along with obesity, other coexisting conditions such as high blood pressure, diabetes mellitus and, most significantly, advanced age are associated with increased COVID-19 severity, possibly due to an underlying chronic inflammatory state or a lower threshold for the development of organ dysfunction as a result of the immune response [ 37 , 38 , 39 ]. All of the above-mentioned illnesses, as well as old age and a chronic inflammatory state, have been linked to a deficient magnesium level.…”
Section: Discussionmentioning
confidence: 99%
“…Palaiodimos et al reported that patients with severe obesity were more likely to undergo intubation (BMI < 25 kg/m²: 18.4%, BMI 25-34 kg/m²: 16.4%, BMI ≥ 35 kg/m²: 34.8%, p = 0.032). Overall, 45% of the patients had increasing oxygen requirements during their hospital stay, but with no significant differences between BMI categories (56). Simmonet et al in a monocentric retrospective study involving 124 patients who were admitted to the ICU with confirmed SARS-CoV-2 infection at Roger Salengro Hospital at the "Center Hospitalier Universitaire de Lille" (CHU 27), concluded that the distribution of BMI categories differed significantly between those who needed mechanical ventilation and those who did not (p < 0.01, Fisher for trend accurate test).…”
Section: Obesity In Patients With Covid-19 and Likelihood Of Intubationmentioning
confidence: 93%
“…Palaiodimos et al reported that 24% of 200 patients with COVID-19 in their retrospective study died during hospitalization, and that the mortality rate was higher in patients with severe obesity, specifically, BMI < 25 kg/m²: 31.6%, BMI 25-34 kg/m²: 17.2%, BMI ≥ 35 kg /m²: 34.8%, p = 0.03 (56). Similar results were reported by Van Halem et al who studied 319 patients aged 16 years or older, hospitalized for at least 24 hours with confirmed COVID-19 infection by April 15 at a tertiary care center.…”
Section: Obesity In Patients With Covid-19 and Mortalitymentioning
confidence: 96%